Optimizing irrigation scheduling for winter wheat using the AquaCrop model in Xinjiang, China - Fu, Qiuping; Liu, Xueru; Hong, Ming; Ai, Pengrui; Ma, Liang; Zhao, Jinghua; Wang, Quanjiu (Frontiers in Plant Science, 2025)
IntroductionEstablishing an appropriate irrigation schedule is fundamental for the sustainable management of agricultural water resources, effectively alleviating water scarcity and ensuring regional food security.MethodsIn this study, the AquaCrop model was calibrated and validated using field experimental data of winter wheat collected from 2022 to 2024. Irrigation schedules for three typical rainfall years—wet, normal, and dry—were determined, and a multi-objective optimization approach was proposed by coupling the AquaCrop model with the entropy weight method.ResultsThe results showed that the AquaCrop model accurately simulated canopy cover, aboveground biomass, soil water storage, and yield of winter wheat. To achieve the maximum yield, 15, 16, and 18 irrigation events were required in wet, normal, and dry years, respectively, with an irrigation quota of 30 mm per event and a lower soil water content threshold maintained at 50% of readily available water (RAW). In contrast, when the objective shifts from maximizing yield to maximizing water use efficiency (WUE), the highest WUE was achieved with 3, 4, and 5 irrigations in wet, normal, and dry years, respectively, with RAW thresholds of 90%, 90%, and 80%, and an irrigation quota of 80 mm. When considering multi-objective optimization to minimize irrigation water while maximizing yield and WUE, the recommended irrigation schedules were 3 irrigations for wet years and 4 irrigations for both normal and dry years, with RAW thresholds of 90%, 90%, and 110%, respectively, and an irrigation quota of 80 mm.DiscussionThe findings provide a theoretical basis and technical support for developing optimized irrigation schedules and making informed irrigation decisions for winter wheat in arid regions.